1995
DOI: 10.1289/ehp.95103s625
|View full text |Cite
|
Sign up to set email alerts
|

Environmental health and Hispanic children.

Abstract: There are numerous indicators that Hispanics face a disproportionate risk of exposure to environmental hazards. Ambient air pollution, worker exposure to chemicals, indoor air pollution, and drinking water quality are among the top four threats to human health and are all areas in which indicators point to elevated risk for Hispanic populations. These data, juxtaposed with data on the health status of Hispanics, tell us that the environmental health status of Hispanics and their children is poor. At the same t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…The research that does exist on the Hispanic population as a whole indicates this population typically suffers from poor air quality, pesticides, dump sites, and contaminated drinking water (Nieves and Wernette 1992). Metzger, Delgado, and Herrell (1995) determine that the environmental health status of Hispanics and their children is poor. Hispanic populations have an elevated chance of health risks caused by worker exposure to chemicals and to indoor and outdoor pollution.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The research that does exist on the Hispanic population as a whole indicates this population typically suffers from poor air quality, pesticides, dump sites, and contaminated drinking water (Nieves and Wernette 1992). Metzger, Delgado, and Herrell (1995) determine that the environmental health status of Hispanics and their children is poor. Hispanic populations have an elevated chance of health risks caused by worker exposure to chemicals and to indoor and outdoor pollution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors point out that significant inadequacies in the collection of data on Hispanics-especially ascertaining large enough data samples-make it difficult to improve Hispanic environmental health status. They charge the U.S. Environmental Protection Agency (EPA) with addressing these environmental problems and use a healthbased approach to reach environmental justice (Metzger, Delgado, and Herrell 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…21,43,[63][64][65] Latino adolescents are more likely to use drugs, alcohol, and tobacco 21,43,66 ; less likely to use contraceptives 67,68 ; more likely to be injured 21,43,66 ; and more likely to attempt suicide thanAfricanAmerican and non-Hispanic White adolescents.…”
Section: Why Latino Children? Why Now?mentioning
confidence: 99%
“…4,5,13,14,[118][119][120][121] Current federal and state data systems are also limited in terms of Latino child health indicators. 64 A systematic review of approximately 200 studies on Latino children revealed several methodologic limitations: more than 60% of the studies did not report a method of ethnic identification; most reported data for Hispanics as an overall group; and almost half did not report an indicator for socioeconomic status. Also, because more than 50% of the studies involved secondary data, there was often an absence of relevant medical and nonmedical factors to explain the findings.…”
Section: Pitfalls In Latino Subgroup Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation